2020
DOI: 10.1371/journal.ppat.1008569
|View full text |Cite
|
Sign up to set email alerts
|

Host cytosolic RNA sensing pathway promotes T Lymphocyte-mediated mycobacterial killing in macrophages

Abstract: Mycobacterial infection leads to activation of the RIG-I/MAVS/TBK1 RNA sensing pathway in macrophages but the consequences of this activation remains poorly defined. In this study, we determined that activation of this RNA sensing pathway stimulates ICAM-1 expression in M.avium-infected macrophage through the inhibition of the E3 ubiquitin ligase CRL4 COP1/DET1 . CRL4 when active targets the transcription factor ETV5 for degradation by the ubiquitin-proteasome system. In the absence of the ETV5 transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Cheng et al indicated that the host cytosolic RNA sensing pathway stimulates ICAM-1 expression through the inhibition of CRL4 COP1/DET1 , an E3 ubiquitin ligase, and promotes T Lymphocyte-mediated mycobacterial killing in macrophages. 30 Jia et al found that Gal9 can be recruited by impaired lysosomes to regulate ubiquitination and contribute to autophagic control during Mtb infection. 31 Additionally, Chai et al demonstrated that Mtb surface protein Rv1468c could recruit ubiquitin to trigger host xenophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al indicated that the host cytosolic RNA sensing pathway stimulates ICAM-1 expression through the inhibition of CRL4 COP1/DET1 , an E3 ubiquitin ligase, and promotes T Lymphocyte-mediated mycobacterial killing in macrophages. 30 Jia et al found that Gal9 can be recruited by impaired lysosomes to regulate ubiquitination and contribute to autophagic control during Mtb infection. 31 Additionally, Chai et al demonstrated that Mtb surface protein Rv1468c could recruit ubiquitin to trigger host xenophagy.…”
Section: Discussionmentioning
confidence: 99%
“…No. M198; HiMedia Laboratories) containing 10% OADC (oleic acid/albumin/dextrose/catalase, 0.05% Tween 80) as we did previously [12] until midexponential phase. Prior to use, bacterial culture was passed through a syringe fitted with a 27‐gauge needle at least 10 times.…”
Section: Methodsmentioning
confidence: 99%
“…No. M198; HiMedia Laboratories) containing 10% OADC (oleic acid/albumin/dextrose/catalase, 0.05% Tween 80) as we did previously [12] until midexponential phase.…”
Section: Bacterial Culturementioning
confidence: 99%
“…Host cytosolic RNA-sensing pathways play a critical role in sensing the DNA and RNA of intracellular pathogens, including Listeria monocytogenes and M. tuberculosis (Mtb) ( 34 , 35 ). The host cytosolic RNA-sensing pathway facilitates T cell-mediated bacterial killing in M. avium -infected macrophages ( 36 ). In macrophages, RNA released from MAC-containing phagosomes and retinoic acid inducible gene-I (RIG-I) recognizes the released RNA ( Figure 2 ).…”
Section: Understanding the Innate Immune Response To Mac Infectionmentioning
confidence: 99%
“…The nuclear translocation of ETV5 induces the expression of intracellular adhesion molecule-1 (ICAM-1) which, along with type I interferon expression, induces T lymphocyte-mediated mycobacterial killing in macrophages. In contrast to Mtb infection, activation of the host RNA-sensing pathway provides host protection against M. avium infection ( 36 ).…”
Section: Understanding the Innate Immune Response To Mac Infectionmentioning
confidence: 99%